2009
DOI: 10.1093/bja/aen364
|View full text |Cite
|
Sign up to set email alerts
|

Heated lidocaine/tetracaine patch (Synera™, Rapydan™) compared with lidocaine/prilocaine cream (EMLA®) for topical anaesthesia before vascular access

Abstract: The lidocaine/tetracaine patch provided effective anaesthesia with an application time as short as 10 min and was better than lidocaine/prilocaine cream at all application times shorter than 60 min, demonstrating a substantial improvement in time to onset of anaesthesia. The lidocaine/tetracaine patch provided an important alternative to lidocaine/prilocaine cream for topical local anaesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
1
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 12 publications
3
58
1
5
Order By: Relevance
“…Upon removal from the protective pouch and exposure to atmospheric oxygen, an exothermic reaction occurs causing the patch heat up and increasing skin temperature bỹ 5C [173]. The effectiveness of the heat-aided patches was first demonstrated in adults [174], and the device was commercialized as Synera TM (USA) or Rapydan TM (Europe) and approved for paediatric use [175]. The surface area of the patch is 50 cm 2 but drug is delivered through only 10 cm 2 .…”
Section: Innovative Methods For Paediatric Transdermal Drug Deliverymentioning
confidence: 99%
“…Upon removal from the protective pouch and exposure to atmospheric oxygen, an exothermic reaction occurs causing the patch heat up and increasing skin temperature bỹ 5C [173]. The effectiveness of the heat-aided patches was first demonstrated in adults [174], and the device was commercialized as Synera TM (USA) or Rapydan TM (Europe) and approved for paediatric use [175]. The surface area of the patch is 50 cm 2 but drug is delivered through only 10 cm 2 .…”
Section: Innovative Methods For Paediatric Transdermal Drug Deliverymentioning
confidence: 99%
“…These studies showed that the warm lidocaine and tetracaine patch had a more rapid analgesic effect than EMLA cream, acting in 30 minutes instead of 60 minutes. However, apart from the time it took for them to start providing pain relief, both formulations were equally effective (9,10).…”
Section: Accepted Articlementioning
confidence: 99%
“…We know how long it would be before they took effect, so the warm lidocaine and tetracaine patches and the EMLA cream were applied at least 30 and 60 minutes, respectively, before the needle procedure (10). The topical analgesics were removed immediately before the needle procedure.…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation
“…This anesthetic is available commercially as a 2 or 3% solution with 1:50,000 to 1:100,000 epinephrine [4][5][6][7] . Different forms of lidocaine have been developed for use as topical anesthetics.…”
Section: Introductionmentioning
confidence: 99%